Description of corrections on electrode polarization impedance using isopotential interface factor - Gomez Sanchez, John Alexander (2012)
In this paper, we propose an equation and define the Isopotential Interface Factor (IIF) to quantify the contribution of electrode polarization impedance in two tetrapolar electrode shapes. The first tetrapolar electrode geometry shape was adjacent and the second axial concentric, both probes were made of stainless steel (AISI 304). The experiments were carried out with an impedance analyzer (Solartron 1260) using a frequency range between 0.1 Hz and 8 MHz. Based on a theoretical simplification, the experimental results show a lower value of the IIF in the axial concentric tetrapolar electrode system which caused a lower correction of interface value. The higher value of the IIF in the adjacent electrode system was KEEI (1Hz, 0.28 mS/cm) = 1.41 and decreased when the frequency and conductance were increased, whereas in the axial concentric electrode system was KEEI (1Hz, 0.28 mS/cm) = 0.08. The average isopotential interface factor throughout the whole range of conductivities and frequencies was 0.23 in the adjacent electrode system and 0.02 in the axial concentric electrode system. The index of inherent electrical anisotropy (IEA) was used to present an analysis of electrical anisotropy of biceps brachii muscle in vitro using the corrections of both tetrapolar electrode systems. A higher IEA was present in lower frequency where the variation below 1 kHz was 15 % in adjacent electrode configuration and 26 % in the axial concentric probe with respect to full range. The IIF is then shown that it can be used to describe the quality of an electrode system.